How Is Our Future Climate Projected? - Young Gu Her; Zachary Brym; Ashley Smyth; Elias Bassil (EDIS, 2020)
Climate is the long-term patterns and fluctuations in air and moisture. This 5-page article explains how future climate is projected using mathematical models and introduces common scientific terms used when discussing climate change. Written by Young Gu Her, Zachary Brym, Ashley Smyth, and Elias Bassil, and published by the UF/IFAS Department of Agricultural and Biological Engineering, November 2020.